Nilai-nilai Pendidikan Akhlak Terkait Keutamaan Rasa Malu dalam Kitab Adab Riyadhush Shalihin - Ira Solihah; Ikin Asikin (Jurnal Riset Pendidikan Agama Islam, 2021)
Abstract. The purpose of this study was to determine the values ​​of moral education related to the virtue of shame in the book of adab riyadhush shalihin written by Imam An-Nawawi. This study applies a qualitative descriptive approach using the library research method. Based on the literature study, there are several sources of study, namely primary sources in the form of the book of Riyadhush Shalihin and secondary sources that support this research, information contained in the library and other information. In data analysis using content analysis, namely the method used to draw conclusions through efforts to find the content of the message which is carried out objectively and systematically so that it can be a conclusion that answers the formulation of the problem. This study tries to answer the questions: 1. The essence of education in the book of adab riyadhush shalihin related to the virtue of shame; 2. The concept of strengthening shame character education according to experts; 3. The educational values ​​contained in the book of adab riyadhush shalihin are related to the virtue of shame towards strengthening the character of shame in the personal, community and state spheres. Through content analysis, several points are made. First, the essence of education from the book of adab riyadush shalihin is to cultivate a sense of faith in oneself, that faith will bring forth shame by itself, and shame brings nothing but goodness. Second, the concept of strengthening shame character education is a process in the formation and development of the potential that exists within the individual with the aim of protecting him from disgraceful acts. Third, there are 3 parts of the value of education in the book of adab riyadhush shalihin related to the virtue of shame on character strengthening, namely for oneself, the scope of society and the life of the nation and state. Abstrak. Tujuan penelitian ini adalah untuk mengetahui nilai-nilai pendidikan akhlak terkait keutamaan rasa malu dalam kitab adab riyadhush shalihin yang ditulis oleh Imam An-Nawawi. Penelitian ini menerapkan pendekatan deskriptif kualitatif dengan menggunakan metode library research atau penulisan berdasarkan literatur. Berdasarkan studi kepustakaan terdapat beberapa sumber kajian yaitu sumber primer berupa kitab riyadhush shalihin dan sumber sekunder yang menjadi pendukung dalam penelitian ini, informasi yang terdapat di perpustakaan dan informasi lainnya. Dalam analisis data menggunakan analisis isi (content analysis) yang mana merupakan cara yang digunakan untuk menarik kesimpulan melalui usaha menemukan kandungan isi pesan yang dilakukan dengan objektif dan sistematis sehingga dapat menjadi kesimpulan yang menjawab rumusan masalah. Penelitian ini berusaha menjawab pertanyaan : 1. Esensi kependidikan dalam kitab adab riyadhush shalihin terkait keutamaan rasa malu; 2. Konsep penguatan pendidikan rasa malu menurut para ahli; 3. Nilai-nilai pendidikan yang terkandung dalam kitab adab riyadhush shalihin terkait keutamaan rasa malu terhadap penguatan rasa malu dalam ruang lingkup pribadi, masyarakat dan negara. Melalui analisis isi dihasilkan beberapa poin. Pertama, esensi kependidikan dari kitab adab riyadush shalihin adalah dengan menumbuhkan rasa iman dalam diri, iman tersebut akan memunculkan rasa malu dengan sendirinya, dan rasa malu tidak membawa apapun selain kebaikan. Kedua, konsep penguatan pendidikan rasa malu adalah sebuah proses dalam pembentukan serta pengembangan potensi yang ada dalam diri individu dengan tujuan melindungi mereka dari melakukan suatu hal yang tercela. Ketiga, terdapat 3 bagian nilai pendidikan dalam kitab adab riyadhush shalihin terkait keutamaan rasa malu terhadap penguatan karakter yakni untuk dirinya sendiri, ruang lingkup masyarakat serta kehidupan berbangsa dan bernegara.